The Economic Effects on Acute Care Surgery in a New York City Public Hospital During the COVID Pandemic. Issue 5 (May 2023) - Moghadamyeghaneh, Zhobin; Ojo, Adedolapo; Rahimi, Murwarid; Kopatsis, Anthony Paul; Kopatsis, Katherine; Kopatsis, Anthony
Background: Since the start of the COVID-19 pandemic, less acute care surgical procedures have been performed and consequently hospitals have experienced significant revenue loss. We aim to investigate these procedures performed before and after the start of the COVID-19 pandemic, as well as their effect on the economy. Methods: This is a retrospective analysis of patients who underwent cholecystectomies and appendectomies during March–May 2019 compared to the same time period in 2020 using Chi-square and t-tests. Results: There were 345 patients who presented with appendicitis or cholecystitis to Elmhurst Hospital Center during the March–May 2019 and 2020 time period. There were three times as many total operations, or about 75%, in 2019 (261) compared to 2020 (84). There was a decrease in the number of admissions from 2019 to 2020 for both acute cholecystitis (149 vs 43, respectively) and acute appendicitis (112 vs 41, respectively). The largest decrease in the number of admissions in 2020 compared to 2019 was observed in April 2020 (98 vs 9, P < .01) followed by May [69 vs 20, P < .01], and March [94 vs 55, P < .01]. Corresponding to the decrease in operative patterns was a noticeable six-time reduction in revenue for the procedures in 2019 ($187, 283) compared to 2020 ($30, 415). Conclusion: We observed almost a triple reduction in the number of cholecystitis and appendicitis procedures performed during the 2020 pandemic surge as compared to the 2019 pre-pandemic data. Elmhurst hospital also experienced four times the loss of revenue during the same time period.